DAMPAK KONFLIK DAN RESOLUSI KONFLIK TERHADAP SISTEM PENDIDIKAN AGAMA ISLAM DI SEKOLAH SONGSERM ISLAM SEKSA PATANI, THAILAND SELATAN - Sulong, Miss. Komareeyah; Machali, Imam (ULUL ALBAB Jurnal Studi Islam, 2016)
This study describes the conflict and its resolution as well as the impact on the system of Islamic Education in Schools Songserm Seksa Islam Patani (SSIS) South Thailand. The discussion focused on three issues. First, how the conflict and its resolution is. Second, how the impacts of the conflict on the education system of the Islamic religion. And third, how the impacts of conflict resolution on the Islamic education system. The results showed that the conflict in Pattani is due to several factors: injustice, discrimination, mistrust each other, the differences of culture, media propaganda, political conflicts and interests. The impact of conflict on the education system in SSIS is the reduction of school hours, the decline of student achievement and teacher performance, the uncertainty caused by the changes of government’s policy on conflict resolution, and the school should be off abruptly during the conflict. While the impact of the conflict resolution toward Islamic Education System in SSIS is the increased quality of teacher performance, the growth of the spirit of educators in the learning process, and a culture of effective and conducive learning in SSIS.